The Antibacterial Activity of Red Dragon Fruit Peel (Hylocereus polyrhizus Britton & Rose) Methanolic Fraction Against Staphylococcus epidermidis and Propionibacterium acnes - Sri Wahdaningsih; Eka Kartika Untari (Universitas Lambung Mangkurat, 2021)
Acnes can be caused by Propionibacterium acnes and Staphylococcus epidermidis. Red dragon (Hylocereus polyrhizus B & R) fruit peels is one of natural materials which is assumed to possess an antibacterial activity. The purpose of this study was to determine the antibacterial activity of red dragon fruit peels methanol fraction (RDFPMF) against S. epidermidis and P. acne by disc diffusion Kirby-Bauer method. Red dragon fruit peels were maceration in chloroform and fractionation in methanol. Clindamycin 4µg/disk was used as positive control and DMSO 10% was used as negative control. This research showed that the RDFPMF has antibacterial activity against P. acnes which the average of inhibition zones obtained from the concentrations from 100, 50, and 25 mg/mL respectively were 10.5 ± 0.50 mm, 10.0 ± 0.00 mm, and 8.5 ± 0.50 mm. The RDFPMF has no inhibition zone toward S. epidermidis. The red dragon fruit peels methanol fraction has antibacterial activity on P. acnes by disc diffusion method (Kirby-Bauer test).